Shazieahna's Hijab Boutique / Norzieyati Dzulkiflie...[et al.] - Dzulkiflie, Norzieyati; Dulla, Nordiyana; Raim, Noor Aziah; Norhady, Sham Nurismanizah (Faculty of Administrative Science and Policy Studies, 2014)
We are starting our own business as partners and deciding to call our business as Shazieahna's Hijab Boutique. Our main activity of business is introducing new style and design of Hi jab. Our hi jab is focus only on 'half-moon' and shawl that cover the 'Aurah' which following the 'Syarak' in Islam. There are several important departments to run our business smoothly, which are administrative department, marketing department, operational department and financial department. Each of us will head one of the departments while there will be one person acts as General Manager, who will be the head of all the departments in our business. We started this business by applying loan where the amount is RM 250, 000. Our office located in our shop lot so that it will easy for us while working. It is located in the One Place Mall, Putatan, Kota Kinabalu, Sabah. We chose this location because nowadays there are many residences that had built in there and many people live at this area. So, we are trying the opportunity to get and attract the customer here.